THE PROBLEM OF GENERATING OPTIMAL CAPITAL STRUCTURE OF AIR TRANSPORT ENTERPRISES IN CONDITIONS OF LIQUIDITY CRISIS - Asanina, A. V.; Bohushko, O. M. (Science and Transport Progress, 2009)
Tendencies of forming the capital structure of enterprises in conditions of the liquidity crisis are analyzed in the article. The basic tendencies of forming the capital structure, which characterize aviation transport enterprises, are determined. The necessity of using the loan capital and its peculiarities are also investigated.